STRATEGI PEMASARAN TOKO ODY.SUB MELALUI PLATFORM DIGITAL (Analisis Marketing Mix 4P pada Instagram, Shopee, dan TikTok) - annin_29; Aditya Fahmi Nurwahid (The Commercium, 2025)
This study aims to explore the marketing strategies employed by Ody.Sub through digital platforms, including Instagram, Shopee, and TikTok. Ody.Sub is a well-known thrifting store located in Sleman City, recognized as atrendsetter in the thrift fashion scene since its establishment in 2019. A qualitative descriptive method was used to analyze the store's marketing activities, with data collected through interviews, observations, and documentation. This researchadopts a comprehensive approach by examining the 4P elements of the marketing mix: product, price, place, and promotion. The study presents findings in the form of descriptive text. Overall, Ody.Sub has effectively integrated the 4P marketing mix elements into its digital promotion strategy, leveraging the strengths of Instagram and TikTok to attract customers while utilizing Shopee to facilitate purchasing processes. However, there are areas that require further attention and improvement. Additionally, this research concludes that Ody.Sub’s application of media convergence through stages of cross-promotion, cloning, coopetition, content sharing, and full convergence enables more efficient information distribution and broader audience reach